2002
DOI: 10.1002/1521-3757(20020715)114:14<2655::aid-ange2655>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Photoaktivierbare, synthetische Ras-Proteine als „Köder“ für die Identifizierung Plasmamembran-assoziierter Bindungspartner des Ras-Proteins

Abstract: Die Regulation von Wachstums-und Differenzierungsprozessen durch die Proteine der Ras-Superfamilie [1] ist unabdingbar mit der korrekten subzellul‰ren Verteilung dieser kleinen Guanosintriphosphat(GTP)-Bindungsproteine ver-kn¸pft. [2] Die Ras-Proteine selbst kˆnnen ihre biologische Funktion nur dann wahrnehmen, wenn sie an der Plasmamembran der Zelle lokalisiert sind. Die Voraussetzung f¸r die erfolgreiche Adressierung bilden dabei posttranslationale Modifizierungen der Ras-Proteine wie S-Farnesylierung und S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…We have synthesized several N‐Ras peptides carrying the maleimido group with different combinations of lipid patterns ( 22 – 24 ), such as the farnesylated and palmitoylated peptide 22 or the double farnesylated compound 24 (Figure 7a). Ras proteins bearing a photoactivatable benzophenone group are efficient tools to study the interaction and cross‐linking with possible Ras‐binding proteins 18. The interest in such proteins led us to synthesize lipidated peptides 25 and 26 carrying the benzophenone group (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
“…We have synthesized several N‐Ras peptides carrying the maleimido group with different combinations of lipid patterns ( 22 – 24 ), such as the farnesylated and palmitoylated peptide 22 or the double farnesylated compound 24 (Figure 7a). Ras proteins bearing a photoactivatable benzophenone group are efficient tools to study the interaction and cross‐linking with possible Ras‐binding proteins 18. The interest in such proteins led us to synthesize lipidated peptides 25 and 26 carrying the benzophenone group (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis of the biological response for the 11bpt conjugate showed that the transforming potential of the semisynthetic protein is ca. one-third the potential of full-length RasG12V . This activity is high enough to conclude that the processing of the BP-labeled mutant is not essentially altered.…”
Section: Resultsmentioning
confidence: 87%
“…Given the fact that the mechanisms of Ras palmitoylationand thereby the mechanisms for its localization to the plasma membranecould not be unraveled conclusively, the employment of new techniques extending beyond exisiting methodology appears to be required. “Photoaffinity labeling” (PAL) has gained considerable merit in analyzing protein−protein interactions (Figure ). , In the light of these findings, we reasoned that biologically active Ras proteins incorporating a photoactivatable group could serve as efficient tools 1 General principle of photoaffinity labeling. …”
Section: Introductionmentioning
confidence: 99%
“…Bei diesen Ansätzen wird ein Großteil der Peptidsequenz schnell an einem festen Träger synthetisiert, abgespalten und mit lipidierten Aminosäuren in Lösung verknüpft oder durch Alkylierung freier Thiolseitenketten im Cystein lipidiert. Solche Methoden sind recht häufig eingesetzt worden und waren besonders erfolgreich bei prenylierten Peptiden, wie Beiträge der Arbeitsgruppen um Naider,19, 35 Gelb,3638 Poulter39 und Waldmann gezeigt haben 4043…”
Section: Synthese Lipidierter Ras‐ Und Rab‐peptideunclassified
“…Hierbei wurden Isoprenoidfragmente im Farnesylrest substituiert, wobei die Modifizierung mit Benzophenongruppen die Isoprenoidfunktion nicht zu beeinträchtigen schien. Die biologische Aktivität Benzophenon‐modifizierter Ras‐Konstrukte konnte dementsprechend in einem zellulären Testsystem nachgewiesen werden, bei dem Phäochromozytomzellen (PC 12) nach Mikroinjektion onkogener Ras‐Mutanten mit einer Isopren‐Benzophenon‐Modifikation zu einem Neurit‐artigen Zelltyp differenzierten 40. Die Benzophenon‐Ras‐Lipoproteine zeigten nach Stimulation mit Sos eine erhöhte Nucleotidaustauschaktivität und lieferten nach Aktivierung eines Ras‐Sos‐Gemischs mit UV‐Licht ein spezifisches Kupplungsprodukt 41…”
Section: Ras‐proteine Als Reagentien In Der Zellbiologieunclassified